Violence Against Women and Immigrant Workers - Santika, Sela; Yusuf , Hudi (Jurnal Multidisiplin Indonesia, 2024)
The resistance can be represented by who is responsible and can be known where Saia is. Navavo's most vulnerable are swayed by corruption, whether it's violence that is reported in the public maurua domain of violence. Having seen both physical violence and economic displacement, as well as sexual violence and baddest violence, women are Eria Wadi's focus. These markings. Because work becomes innocent of the violence. Even the violence they control can increase or decrease from one type of violence within a time together.Because of ven dab's education, kuranenza skills have been developed, and dispossi enabled as a dekeria on wereka serina is awarded as a state-owned pablum that always contributes the largest economy, varun kenedulian to, they so., violence against women has a variety of effects on victims, physically and psychologically. Psychologically, victims commonly experience low self-esteem, guilt, a tendency to blame themselves, deep sadness, a feeling of not wanting to go through life (depression) and post-traumatic stress disorder. On the other hand, the effects of this psychic disorder led to the risk of drug addiction such as narcotics, smoking, and alcohol increase. The Indonesian nation, as part of the world community, has accepted the gender equality movement. They are consistent with the values contained in Pancasila, the state philosophy. But so far, violence against women still frequently occurs, especially against women in socially vulnerable economies, including women migrant workers. Ironically, violence against women migrant workers is not only done by others who have no family relationship with the victim (the employer) but also by their own families before they become migrant workers. For some women migrant workers, migrant workers the choice to be truly meant a way out of suffering in the family. But the tragedy in the workplace is that they actually get into the trap of violence. Therefore, the empowerment of women is still very relevant and even urgent and conducted comprehensively.